HIV-1 Group O Integrase Displays Lower Enzymatic Efficiency and Higher Susceptibility to Raltegravir than HIV-1 Group M Subtype B Integrase - Depatureaux, Agnès (Antimicrob Agents Chemother, 2014)
HIV-1 group O (HIV-O) is a rare HIV-1 variant characterized by a high number of polymorphisms, especially in the integrase coding region. As HIV-O integrase enzymes have not previously been studied, our aim was to assess the impact of HIV-O integrase polymorphisms on enzyme function and susceptibility to integrase inhibitors. Accordingly, we cloned and purified integrase proteins from each of HIV-1 group O clades A and B, an HIV-O divergent strain, and HIV-1 group M (HIV-M, subtype B), used as a reference. To assess enzymatic function of HIV-O integrase, we carried out strand transfer and 3′ processing assays with various concentrations of substrate (DNA target and long terminal repeats [LTR], respectively) and characterized these enzymes for susceptibility to integrase strand transfer inhibitors (INSTIs) in cell-free assays and in tissue culture, in the absence or presence of various concentrations of several INSTIs. The inhibition constant (K(i)) and 50% effective concentration (EC(50)) values were calculated for HIV-O integrases and HIV-O viruses, respectively, and compared with those of HIV-M. The results showed that HIV-O integrase displayed lower activity in strand transfer assays than did HIV-M enzyme, whereas 3′ processing activities were similar to those of HIV-M. HIV-O integrases were more susceptible to raltegravir (RAL) in competitive inhibition assays and in tissue culture than were HIV-M enzymes and viruses, respectively. Molecular modeling suggests that two key polymorphic residues that are close to the integrase catalytic site, 74I and 153A, may play a role in these differences.